2021
DOI: 10.1029/2020jg006237
|View full text |Cite
|
Sign up to set email alerts
|

Winter Limnology: How do Hydrodynamics and Biogeochemistry Shape Ecosystems Under Ice?

Abstract: The ice-cover period in lakes is increasingly recognized for its distinct combination of physical and biological phenomena and ecological relevance. Knowledge gaps exist where research areas of hydrodynamics, biogeochemistry and biology intersect. For example, density-driven circulation under ice coincides with an expansion of the anoxic zone, but abiotic and biotic controls on oxygen depletion have not been disentangled, and while heterotrophic microorganisms and migrating phytoplankton often thrive at the ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 255 publications
2
32
0
Order By: Relevance
“…Santibáñez et al (2019) showed experimentally that bacteria were preferentially incorporated into lake ice during freezing and that this was mainly controlled by the solute concentration of major ions in the liquid water source; the higher the ion concentration in water the more readily the bacteria were incorporated into the ice. Cryoconcentration, the exclusion of solutes when ice freezes, contributes to an increased solute concentration at the ice-water interface (Jansen et al, 2021), which in turn may favor bacterial incorporation into the ice.…”
Section: 1029/2020jg006233 11 Of 18mentioning
confidence: 99%
“…Santibáñez et al (2019) showed experimentally that bacteria were preferentially incorporated into lake ice during freezing and that this was mainly controlled by the solute concentration of major ions in the liquid water source; the higher the ion concentration in water the more readily the bacteria were incorporated into the ice. Cryoconcentration, the exclusion of solutes when ice freezes, contributes to an increased solute concentration at the ice-water interface (Jansen et al, 2021), which in turn may favor bacterial incorporation into the ice.…”
Section: 1029/2020jg006233 11 Of 18mentioning
confidence: 99%
“…75 Although our measurements captured only the icefree summer behavior of redox-active solutes, it is highly likely that they are inuenced by winter hydrodynamics. 74,76,77 Future studies will be paramount in linking winter hydrodynamics, mixing, and hydrology to biogeochemical cycling in order to determine the effect of decreasing ice cover on methane production within Arctic lake sediments. Previous studies have linked methane transport from active layers of permafrost thaw and ground water into near shore, shallow areas of Toolik Lake.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…Ice can be present or absent, it can cover a lake for a long time or a short time, and it can vary from optically transparent columnar ice ("black ice") to more opaque ("white ice"), all with important implications for biological, chemical, and physical processes. The review and synthesis by Jansen et al (2021) focused on developing an integrative understanding of how physical processes in lakes in winter are linked to biogeochemical and ecological dynamics. Primary drivers such as light availability and distribution of heat within the water column have cascading effects on critical chemical parameters such as redox state, which impacts both nutrients and predominant metabolic processes including aerobic respiration, nitrification-denitrification coupling, methane oxidation (Sawakuchi et al, 2021), and other anaerobic metabolisms such as methanogenesis, sulfate reduction, anoxygenic photosynthesis, and anammox.…”
Section: Concepts and Synthesesmentioning
confidence: 99%